2006
DOI: 10.1093/jn/136.3.769s
|View full text |Cite
|
Sign up to set email alerts
|

Aged Garlic Extract Improves Blood Pressure in Spontaneously Hypertensive Rats More Safely than Raw Garlic

Abstract: We studied the effects of two garlic sources on systolic blood pressure (SBP) using spontaneously hypertensive rats (SHRs). Beginning at 12 wk of age, male SHRs were fed diets containing either aged garlic extract (AGE) or raw garlic (RG) powder for 10 wk. Both AGE and RG reduced the increase of SBP compared with the control group from 4 wk after beginning the experimental diets. The effect of AGE was accompanied by a decrease of pulse pressure (PP), suggesting an improvement of the pliability of the artery, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 19 publications
2
44
0
2
Order By: Relevance
“…The effect of organosulfur compounds on reduced hypertension has been studied. The allicin and organosulfur compounds from aqueous garlic extract administration reduced the systolic blood pressure in fructose-fed rats (Elkayam et al, 2001;Vazquez-Prieto et al, 2010) and in spontaneously hypertensive rats (Harauma and Moriguchi, 2006). The same effect on systolic blood pressure was observed when the allicin from garlic powder was administered to rats fed with a high cholesterol diet (Ali et al, 2000).…”
Section: Effects Of Organosulfur Compounds From Garlic On Animal Expementioning
confidence: 72%
“…The effect of organosulfur compounds on reduced hypertension has been studied. The allicin and organosulfur compounds from aqueous garlic extract administration reduced the systolic blood pressure in fructose-fed rats (Elkayam et al, 2001;Vazquez-Prieto et al, 2010) and in spontaneously hypertensive rats (Harauma and Moriguchi, 2006). The same effect on systolic blood pressure was observed when the allicin from garlic powder was administered to rats fed with a high cholesterol diet (Ali et al, 2000).…”
Section: Effects Of Organosulfur Compounds From Garlic On Animal Expementioning
confidence: 72%
“…The AGE improved blood pressure in spontaneously hypertensive (SHR) rats better than raw garlic [71]. Other reports indicate that in SHRs [72] and humans [73] garlic improved blood pressure.…”
Section: Bioactive Constituents With Cardiovascular and Cerebrovasculmentioning
confidence: 99%
“…Other reports indicate that in SHRs [72] and humans [73] garlic improved blood pressure. The lowering effect of garlic on SHRs was linked to the nitric oxide system being more effective than the renin-angiotensin system [71]. The report of Harauma and Moriguachi [71] suggests that one of the systolic blood pressure-lowering effects of AGE could be by protection and maintenance of the flexibility in the blood vessel and the improvement of erythrocyte deformability.…”
Section: Bioactive Constituents With Cardiovascular and Cerebrovasculmentioning
confidence: 99%
“…Nwokocha et al ( 2011 ) reported that aqueous garlic extract caused a decrease in blood pressure and bradycardia by direct mechanism not involving the cholinergic pathway in both normotensive and 2K-1C rats, suggesting a likely involvement of the peripheral mechanism for hypotension. Studies showed that aged garlic extract improved blood pressure in spontaneously hypertensive rats more safely than raw garlic (Harauma and Moriguchi 2006 ). Harmful effects were observed in rats fed with raw garlic, including a decrease in erythrocytes, increase in reticulocytes and generation of papilloma in the forestomach.…”
Section: Animal Studiesmentioning
confidence: 99%